COMMUNICATION PATTERNS OF INFORMATION DELIVERY ON PREPARATION FOR THE ORGANIZATION OF HAJJ WORSHIP AT THE MINISTRY OF RELIGIOUS AFFAIRS (Qualitative Study on Regular Hajj Pilgrims in Tabalong Regency in 2025) - Muzahid Akbar Hayat; Mardiana; Alfi Syahrin (RADJA PUBLIKA, 2026)
This study analyzes communication patterns in the dissemination of information on the organization of the Hajj pilgrimage by the Ministry of Religious Affairs of Tabalong Regency to Hajj pilgrims in 2025. The study is motivated by the diverse backgrounds of pilgrims in terms of gender, domicile, age, educational level, and occupation. These differences pose significant challenges in information delivery, requiring an adaptive and responsive communication system to ensure the safe, orderly, smooth, and comfortable implementation of the Hajj pilgrimage. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with 10 informants, field observations, and documentation studies. Data analysis is grounded in Communication Accommodation Theory to understand convergence and divergence strategies in conveying Hajj-related information to pilgrims with diverse backgrounds. The findings reveal five main communication patterns: (1) a combination of face-to-face communication and digital platforms, (2) a tiered hierarchical communication system mediated by local actors, (3) adaptive two-way communication, (4) multidimensional channel convergence, and (5) continuous negotiation between hierarchical organizational structures and the need to adapt to pilgrims’ diversity. The challenges identified include cognitive limitations among elderly pilgrims, gaps in digital literacy, limited time and resources, inter-agency fragmentation, and technological complexity that is not fully user-friendly for elderly pilgrims. In conclusion, the communication patterns used in disseminating Hajj organization information by the Ministry of Religious Affairs of Tabalong Regency represent a comprehensive and adaptive communication convergence strategy. This strategy is designed to build trust and ensure shared understanding among highly diverse pilgrims, creating a dynamic, responsive, yet organizationally structured communication system. The study recommends enhancing the use of more elderly-friendly communication technologies, strengthening the role of local mediators, extending the duration of Hajj rituals training (manasik), integrating inter-agency information systems, and developing specialized assistance programs for elderly pilgrims with specific health conditions.